Farmers' perceived effectiveness of indigenous land management practices: a study in semi-arid Ghana. Issue 12 (2nd December 2021) - Tenagyei, Louis; Kanton Osumanu, Issaka
ABSTRACT: Indigenous agricultural land management practices have potentials for soil fertility maintenance and balancing crop nutrient requirements. However, the contribution of indigenous farmland management practices and consequential effects on food production has not been fully addressed in the literature. This study assesses rural farmers' perceived effectiveness of indigenous farmland management practices in semi-arid areas of Ghana. The study employs quantitative methods using interview schedules with farming households and stakeholders in the agricultural sector to generate primary data. The sample consists of 226 heads of farming households from three farming communities and three stakeholders – an agricultural extension officer, a representative of a famer-based organisation and an officer of a non-governmental organisation. The results of the study reveal that multi-cropping, inter-cropping, and animal manure application are the primary indigenous techniques for managing farmlands by farmers. Also, farmers use some modern farming practices, such as improved seeds, composting, inorganic fertilisers and agroforestry. The assessment shows that farmers who combine both practices perceive their crop yields to be higher than those who practice only the modern techniques. The study recommends that priority should be given to educating rural farmers on environmentally-friendly farming techniques by combining useful indigenous agricultural land management practices with modern practices.